Finite Element Analysis of Fluid Flow through the Screen Embedded between Parallel Plates with High Reynolds Numbers. (8th February 2021) - Memon, Abid A.; Alotaibi, Hammad; Memon, M. Asif; Bhatti, Kaleemullah; Shaikh, Gul M.; Khan, Ilyas; Mousa, A. A.
Abstract : This paper provides numerical estimation of Newtonian fluid flow past through rectangular channel fixed with screen movable from 10° to 45° by increasing the Reynolds number from 1000 to 10, 000. The two-dimensional incompressible Navier Stokes equations are worked out making use of the popular software COMSOL MultiPhysics version 5.4 which implements the Galerkin's least square scheme to discretize the governing set of equations into algebraic form. In addition, the screen boundary condition with resistance coefficient (2.2) along with resistance coefficient 0.78 is implemented along with slip boundary conditions applied on the wall. We engaged to find and observe the relationship between the optimum velocity, drag force applied by the screen, and pressure occurred in the channel with increasing Reynolds number. Because of the linear relationship between the optimum velocities and the Reynolds number, applying the linear regression method, we will estimate the linear equation so that future prediction and judgment can be done. The validity of results is doing with the asymptomatic solution for stream-wise velocity at the outlet of the channel with screens available in the literature. A nondimensional quantity, i.e., ratio from local to global Reynolds number Re x / Re, is introduced which found stable and varies from -0.5 to 0.5 for the whole problem. Thus, we are in the position to express the general pattern of the velocity of the particles as well as the pressure on the line passing through the middle of the channel and depart some final conclusion at the end.